Innovation as an immanent attribute of an agile enterprise - Agnieszka Rzepka; Andrzej J. Olak (Institute of Economic Research (IER), 2017)
Each organization faces the challenge of operating in an environment that is unpredictable and turbulent. Emergence of business era caused that change had become a key feature that determines the economic environment of an enterprise. Market environment forces companies to seek strategic orientation that would allow them to use market opportunities and come to grips with growing customer demands. These goals can only be achieved by an organization that bears the hallmarks of agility. The purpose of this article is to analyze relationships between obtaining an ability to be innovative and agility attributes of an organization. The problem was analyzed on the basis of empirical research of an international character. The article points out that adopting by a company agility attributes translates into a better competitive position and a higher level of innovation. Innovation in an enterprise constitute an impulse to take new challenges, which perfectly fits into the paradigm of the organization's agility. In turn, through innovation, companies become agile. The presented research confirms that there is a connection between having agility attributes by a company and obtaining by it a high level of innovation. Many authors also specify important role of IT system in introducing product innovations and innovation processes
Keywords: O30; M21; P42; 330; innovation; agile; SME